Discontinuous fiber-reinforced composites : fundamentals and applications - Gandhi, Umesh N.; Goris, Sebastian; Osswald, Tim A.; Song, Yu-Yang (Hanser Publishers ; Hanser Publications, 2020)
{Rovides the theoretical and practical background to design and use discontinuous fiber-reinforced polymer materials, with an emphasis on structural parts for the automotive industry. The product of years of collaborative work between industry and academia is presented in an easy-to-use, comprehensive manner.